China’s Belt and Road Initiative and sustainable development : a case study of China-Serbia relations from 2012 to 2022 - Ferlez, Iva; Garlick, Jeremy; Veselá, Zuzana; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
Serbia became a member of the Chinese Belt and Road Initiative right after its creation in 2013. This initiative invests in various fields, which are also common to fields of the United Nation’s Sustainable Development Goals. This thesis demonstrates how these bilateral relations contributed to Serbia’s sustainability and how the involvement in the Belt and Road Initiative impacted the relations. This is achieved by outlining the main projects of the Belt and Road Initiative, which were planned or already built in Serbia. The projects are focused on the following fields: economy, infrastructure, health, environment, and education. The observed timeframe is following the 2012-2022 period. The Belt and Road initiative is funded by several state-owned Chinese banks which claim that the projects should respect the sustainability of the countries. The findings imply that the involvement of the Belt and Road Initiative positively contributed to the education and health-related goals of sustainable development. However, Serbia’s borrowings from Chinese banks deteriorated the sustainability in other fields observed in this thesis. On the other hand, the Serbian public’s opinion is ever-increasing due to the medical aid China provided during the COVID-19 pandemic. There are doubts about how Serbia will be able to return these borrowings in the future and who should be at fault.
Vedoucí práce: Jeremy Alan Garlick
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor bakal. práce]; bakalářské práce; bachelor's theses